Library wars. 4 : love & war - Yumi, Kiiro (Shojo beat manga., 2011)
In the near future, the federal government creates a committee to rid society of books it deems unsuitable. The libraries vow to protect their collections, and with the help of local governments, form a military group to defend themselves---the Library Forces! Iku and Commander Inamine are abducted by Bakushu-kai terrorists, who demand sensitive material from the library's protected collection in return for the hostage! Dojo is worried about Iku, his problem student with limited field experience. But what Iku lacks in training she more than makes up for in gumption, and she is not going to let library material go without a fight!